Velikoprostorsko strateško načrtovanje za trajnostni razvoj gozdov - Kovač, Marko (Gozdarski vestnik, 2004)
The aim of the third part is to verify, if the presented planning model can beused in the real world. The Kocevska region was chosen as a test site. The article presents the working methods, current conditions, goals and objectivesand strategies for managing forest roles.
Keywords: analiza stanja; analysis of present conditions; developing strategies; oblikovanje ciljev; razvoj strategij; shaping goals and objectives